2022
DOI: 10.1002/admt.202101635
|View full text |Cite
|
Sign up to set email alerts
|

Thermoconformable, Flexible Lithium‐Ion Batteries

Abstract: This work introduces a scalable method for fabrication of flexible, thermoconformable lithium‐ion batteries, suitable for the interior of vehicles. Electrodes with a composite structure are fabricated by combining conventional granular slurries with a porous carbon nanotube fabric current collector and a solid gel polymer electrolyte. The composite structure reduces polarization at high current densities, for example, with 50% and 17% higher charge capacity at 1C in LTO/Li half cells than control samples and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[17] In addition, CNTs are mechanically strong and lightweight, making them useful for portable and flexible devices, where weight and flexibility are concerns such as wearable devices. [18][19][20][21] Li et al investigated binder-free electrodes with advantages such as flexibility and high energy density. [22] The authors employed a hierarchical configuration of electrode active materials with a network of single-walled carbon nanotubes (SWCNTs) as a support and reduced graphene oxide sheets as a conductive additive.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In addition, CNTs are mechanically strong and lightweight, making them useful for portable and flexible devices, where weight and flexibility are concerns such as wearable devices. [18][19][20][21] Li et al investigated binder-free electrodes with advantages such as flexibility and high energy density. [22] The authors employed a hierarchical configuration of electrode active materials with a network of single-walled carbon nanotubes (SWCNTs) as a support and reduced graphene oxide sheets as a conductive additive.…”
Section: Introductionmentioning
confidence: 99%
“…Such morphology is particularly relevant in battery electrodes, where integrating two nanomaterials�a current collector and an electrochemically active material�into a single structure not only maximizes the stress/charge transfer between the building blocks but also eliminates the need for polymeric binders, additives, or metallic current collectors while enhancing battery performance. 23,24 The absence of a metallic foil current collector enables the fabrication of complex-shaped devices such as multifunctional structural batteries for vehicles 25 and thin, flexible, and stretchable batteries. 9,26 In our prior work, we showed that integrating an inorganic phase (namely, MoS 2 ) into a preformed network of CNTF gives a flexible hybrid electrode.…”
Section: Introductionmentioning
confidence: 99%